Membangun Hubungan Kepercayaan dengan Leads: Peran Interaksi Personal dalam Keberhasilan Pemasaran Produk Perbankan (Studi pada PT. KB Bukopin Cabang Jember) - Arya Dhimas Saputra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study analyzes the critical role of personal interactions in building trust and increasing lead-to-customer conversion in banking product marketing. Using a qualitative case study approach at PT. KB Bukopin Jember Branch, data was collected through in-depth interviews with marketers. The results revealed that a hybrid interaction strategy combining digital communication as the initiation and face-to-face interaction, as the peak of engagement, was the most effective approach. The strategy, analyzed through the lens of Symbolic Interaction Theory and Dialogic Communication Theory, was proven to be able to create shared meaning and deeper trust. Marketers emphasized that the quality of persuasive, solution-oriented, and personal interactions was a key component of conversion, far more important than the mere quantity of contacts. An approach focused on value co-creation and social capital investment successfully shifted the relationship dynamics from transactional to collaborative, building long-term loyalty. Furthermore, the findings also identified significant obstacles, such as lead fatigue with generic approaches and sales target pressures that conflict with relational strategies. As an implication, this study recommends strategic investment in soft skills training for marketers and the enhancement of CRM systems to become proactive and personalized platforms to support sustainable relationship marketing strategies.